2011
DOI: 10.1007/s00122-010-1524-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering of major genetic factors generating naturally occurring variation in heading date among Asian rice cultivars

Abstract: To dissect the genetic factors controlling naturally occurring variation of heading date in Asian rice cultivars, we performed QTL analyses using F2 populations derived from crosses between a japonica cultivar, Koshihikari, and each of 12 cultivars originating from various regions in Asia. These 12 diverse cultivars varied in heading date under natural field conditions in Tsukuba, Japan. Transgressive segregation was observed in 10 F2 combinations. QTL analyses using multiple crosses revealed a comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 45 publications
(80 reference statements)
6
60
0
1
Order By: Relevance
“…However, it appears that prezygotic barriers do not intrinsically impair crossing among Asian rice cultivars, because they are easily crossed with one another (Chu et al 1969). Rather, geographical and temporal isolation (particularly variation in Xowering time; e.g., Ebana et al 2011) may be important prezygotic barriers in rice.…”
Section: Discussionmentioning
confidence: 93%
“…However, it appears that prezygotic barriers do not intrinsically impair crossing among Asian rice cultivars, because they are easily crossed with one another (Chu et al 1969). Rather, geographical and temporal isolation (particularly variation in Xowering time; e.g., Ebana et al 2011) may be important prezygotic barriers in rice.…”
Section: Discussionmentioning
confidence: 93%
“…In rice, polymorphism in Hd1 protein, the type of Hd3a promoter and the level of Ehd1 expression were related to diversity of flowering time and geographic adaptation in cultivated rice species (66). Ebana et al (67) found that functional polymorphisms in several identified key genes (Hd1, RFT1, and Ghd7) contributed greatly to the diversity of rice heading dates. Table S2).…”
Section: E1 Locus Was Delimited To a 174-kb Region That Contained A mentioning
confidence: 99%
“…The SSR markers were selected from those described in McCouch et al (2002) and the International Rice Genome Sequencing Project (2005). Polymorphisms were detected as described by Ebana et al (2011). Genomic DNA was extracted from leaves of each plant by the cetyl trimethylammonium bromide method.…”
Section: Quantitative Trait Loci Analysismentioning
confidence: 99%